Defined host factors support HBV infection in non‐hepatic 293T cells. Issue 4 (12th January 2020) - Yang, Xiaoqiang; Cai, Weiwen; Sun, Xiaoyue; Bi, Yanwei; Zeng, Chui; Zhao, XiaoYu; Zhou, Qi; Xu, Tian; Xie, Qingdong; Sun, Pingnan; Zhou, Xiaoling
Abstract: Hepatitis B virus (HBV) is a human hepatotropic virus. However, HBV infection also occurs at extrahepatic sites, but the relevant host factors required for HBV infection in non‐hepatic cells are only partially understood. In this article, a non‐hepatic cell culture model is constructed by exogenous expression of four host genes (NTCP, HNF4α, RXRα and PPARα) in human non‐hepatic 293T cells. This cell culture model supports HBV entry, transcription and replication, as evidenced by the detection of HBV pgRNA, HBV cccDNA, HBsAg, HBeAg, HBcAg and HBVDNA. Our results suggest that the above cellular factors may play a key role in HBV infection of non‐hepatic cells. This model will facilitate the identification of host genes that support extrahepatic HBV infection.